Increasing Diagnostic Potential in Pediatric Optometry by Electrophysiological Methods - Lovasik, J V; Woodruff, M E (Canadian Journal of Optometry, 1983)
With the advent of modern-day technology light-induced electrical activity in the retina and visual cortex can be measured clinically to assess visual function. The Electroretinogram (ERG) and the Visually Evoked Response (VER) are now routine clinical tests used to evaluate the physiological integrity of retinal and visual cortical mechanisms respectively. The theory, and application of these non-invasive, objective tests in the evaluation of various aspects of vision in infants and children are discussed. Numerous case reports are presented to illustrate the extended diagnostic capability afforded the pediatric optometric practitioner by the ERG and VER.